2022
DOI: 10.3390/jcm11030810
|View full text |Cite
|
Sign up to set email alerts
|

How Does Contraceptive Use Affect Women’s Sexuality? A Novel Look at Sexual Acceptability

Abstract: Among the components of a healthy life, sexuality is essential, contributing to both the psychophysical and social well-being of women and, consequently, to their quality of life. A poorly investigated standpoint is the acceptability of contraceptive methods, both in terms of their tolerability and metabolic neutrality and in terms of their impact on sexual life. In this context, we will provide an overview of the different methods of contraception and their effects on female sexuality, from biological changes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…The World Health Organisation (WHO) defines FP as a voluntary decision by an individual or a couple to decide on the number of children to have and when to have them [ 8 ]. As such, control of fertility is key in steering women toward great health benefits including personal, economic, and cultural autonomy to psychological and physical welfare [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organisation (WHO) defines FP as a voluntary decision by an individual or a couple to decide on the number of children to have and when to have them [ 8 ]. As such, control of fertility is key in steering women toward great health benefits including personal, economic, and cultural autonomy to psychological and physical welfare [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The contraception methods (non-medical and medical) had no influence on SQOL results. Furthermore, large cross-sectional and longitudinal studies “have not shown a correlation of[ sic ] medical contraceptive methods (hormonal and intrauterine devices) and sexual function in women” ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The collected reasons are women’s perceptions, unproven but sufficient for them to decide to remove the implant. Changes in bleeding pattern is well-documented in the scientific literature ( 30 , 31 ), however, there is no consistent evidence of the effect of the implant on weight gain ( 32 ) on mood ( 33 , 34 ) or libido and sexual function ( 35 ), and it has even been found that perceived weight gain may be inaccurate and poorly correlated with actual weight ( 36 ). The mood disturbance and cessation of sexual intercourse was the seconds most frequently cited reasons for implant removal, but as in all cases this reason was accompanied by unsatisfactory bleeding; we cannot discriminate which of these reasons was more important in the woman’s decision.…”
Section: Discussionmentioning
confidence: 99%